THE DEVELOPMENT OF INFORMATION TECHNOLOGY OF STRUCTURAL HEALTH MONITORING SYSTEMS - M. V. Emelianov (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives. The aim of the study is to develop information technology design systems for monitoring load-bearing structures of buildings and structures of a higher category of responsibility based on the initial data on the construction object and the results of engineering surveys.Method. The article discusses the approach to the formalization of the description of the procedure for developing projects for monitoring buildings and structures, based on the design features of the SMC building structures, the engineering experience of designing these systems.Result. The article presents the conceptual foundations of the developed information technology, the algorithm for determining the monitoring mode based on information about the construction object, the algorithm for the macro to determine the most loaded nodes and elements in the complex finite element modeling. Recommendations are given for determining the control parameters, the composition of the measuring equipment.Conclusion. The conceptual foundations of information technology developed in the course of the research allow for the further development of algorithms and programs for the automated analysis of information about the object and the construction site in order to obtain the automatic mode of the results necessary for developing monitoring systems for buildings and structures of a higher category of responsibility.